Feasibility Research of Teaching Materials of Appreciation Study of Fiction Prose Based on Makassar Local Wisdom - Haslinda Haslinda (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to create teaching materials for the study of prose fiction based on Makassar local wisdom that are appropriate or valid for students of the Indonesian Language and Literature Education Study Program at the Muhammadiyah University of Makassar. This type of research is research and development or Research and Development (RD) using the ADDIE model (Analyze, Design, Develop, Implement, Evaluation). The subjects of this study were two experts (experts) who assessed the teaching materials. Data collection techniques include test techniques, questionnaires, observations, interviews, and documentation. The data analysis technique used descriptive qualitative analysis techniques and descriptive statistics. Based on the results of this study, it was found that teaching materials for the study of prose fiction based on Makassar local wisdom were feasible or valid in terms of the elements of teaching materials (4.32) or with a very decent category, presentation elements (4.07) or with appropriate categories, graphic elements ( 4,33) or with a very decent category, and linguistic elements (4,19) or with a decent category.